HENMT1 promotes the proliferation and migration of gastric cancer by activating the PI3K-AKT-mTOR signaling pathway - YANG Na; LIU Junli; BAI Jing; YANG Siyi; HAN Jiming; ZHANG Huahua (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2025)
Objective·To investigate the role of HEN methyltransferase 1 (HENMT1) in the proliferation and migration of gastric cancer (GC) and its potential molecular mechanisms.Methods·The expression of HENMT1 in GC was examined using bioinformatics databases, Western blotting and quantitative real-time PCR (qPCR). Kaplan-Meier Plotter and BEST online tools were used to analyze the correlations between HENMT1 expression and overall survival, perineural invasion, subtypes, tumor location and Lauren classification in clinical GC patients. GC cells were cultured in vitro and treated with small interfering RNA (siRNA) targeting HENMT1 and HENMT1 overexpression vectors, in combination with a PI3K activator (740 Y-P) or PI3K inhibitor (3-MA). The roles of HENMT1 in GC cell proliferation and migration were assessed using cell counting kit-8 (CCK-8) assay, colony formation assay, wound healing assay and Transwell migration assay.Results·HENMT1 was significantly upregulated in GC and positively associated with perineural invasion. Its expression was closely related to GC subtypes, being most pronounced in the proliferative subtype, and was higher in intestinal-type GC according to the Lauren classification. However, HENMT1 expression showed no significant correlation with overall survival or tumor location (including gastric body, cardia, antrum and whole stomach). Functional experiments demonstrated that silencing HENMT1 inhibited GC cell proliferation and migration, whereas overexpression of HENMT1 enhanced these capabilities. Mechanistically, silencing HENMT1 reduced the levels of phosphorylated PI3K, AKT and mTOR, as well as their total protein expression. Conversely, HENMT1 overexpression upregulated these proteins. Moreover, siHENMT1 combined with the PI3K activator 740 Y-P effectively reversed the proliferation and migration effects induced by 740 Y-P, while overexpressed HENMT1 combined with the PI3K inhibitor 3-MA reversed the suppressive effects of 3-MA on GC cell proliferation and migration.Conclusion·HENMT1 is highly expressed in GC and positively regulates the proliferation and migration of gastric cancer cells by activating the PI3K-AKT-mTOR signaling pathway.